Kajian Sosial Kepesantrenan dalam Bingkai Varian Teori Praktis: Sebuah Refleksi - Auliya Ridwan (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
As an Islamic educational institution rooted in the history and culture of the archipelago, Pesantren have become the object of academic discourse within social sciences. Within various diverse social arrangements, pesantren have distinctive dimensions that distinguish one pesantren from another. Some of the objects of pesantren social studies include the social relationship between the pesantren and the community outside the pesantren, pedagogy in the educational process, and social changes as the impact of the presence of pesantren and their own elements. This article discusses the framing of social phenomena related to pesantren within the framework of Bourdieu and Giddens' theory of practices, which notably have different approach on structuration. Bourdieu applies structuration through power and Giddens through in the knowledgeability. The use of these two structuration paradigms can shed light on the preservation and changes in agent’s control. However, only conscious phenomena can be framed. Unconscious phenomena apparently cannot be framed in structuration and require assistance from other scientific disciplines, such as psychological anthropology, to explain the phenomena scientifically.